Komunikasi Perawat Dalam Menurunkan Kecemasan Anak Selama Hospitalisasi : Mixed Method Study - Rezkiki, Fitrianola; Utami, Dinaliza; Nugraita, Tri Wilya (Universitas Fort De Kock Bukittinggi, 2022)
Background: Children who undergo hospitalization will experience anxiety. It is caused by separation, loss of control, fear of living in a foreign environment and pain in the body. Communication by nurses can help children and their families to communicate their feelings more effectively so that anxiety is reduced. This study aims to determine and analyze how nurses communicate in reducing children's anxiety during hospitalization. Methods: This study uses a mixed methods study with a sequential explanatory strategy approach. The sample is 84 respondents for quantitative data with accidental sampling technique. While the qualitative data sample amounted to 6 people with purposive sampling technique. Research instruments in the form of questionnaires and interview guidelines. The validity test of the 20 statement therapeutic communication questionnaire is 0.361 and the reliability value is 0.901. Results: The results showed that most of the respondents (58.3%) assessed that nurse communication was not good. While the results of the indept interview obtained two themes; “The need for accurate and reliable information